2017
DOI: 10.1073/pnas.1707098114
|View full text |Cite
|
Sign up to set email alerts
|

Injection of T3SS effectors not resulting in invasion is the main targeting mechanism of Shigella toward human lymphocytes

Abstract: The enteroinvasive bacterium Shigella is a facultative intracellular bacterium known, in vitro, to invade a large diversity of cells through the delivery of virulence effectors into the cell cytoplasm via a type III secretion system (T3SS). Here, we provide evidence that the injection of T3SS effectors does not necessarily result in cell invasion. Indeed, we demonstrate through optimization of a T3SS injection reporter that effector injection without subsequent cell invasion, termed the injection-only mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
(35 reference statements)
0
23
1
Order By: Relevance
“…The capacity of diverse pathogens to inject effector molecules into uninfected host cell populations represents an important mechanism that acts in trans to modify host function (Autenrieth et al, 2010; Pechous and Goldman, 2015; Pinaud et al, 2017). However, the ability to identify and track uninfected but injected cells to determine the consequences of injection remains a technical challenge for many of these microbes.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of diverse pathogens to inject effector molecules into uninfected host cell populations represents an important mechanism that acts in trans to modify host function (Autenrieth et al, 2010; Pechous and Goldman, 2015; Pinaud et al, 2017). However, the ability to identify and track uninfected but injected cells to determine the consequences of injection remains a technical challenge for many of these microbes.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that the injection of T3SS effectors does not inevitably result in cell invasion. 65 Indeed, using an optimized T3SS injection reporter, we demonstrated that effector injection without subsequent cell invasion, termed the "injection-only" mechanism, is the main route of lymphocyte targeting utilized by Shigella. 65 In vitro-activated human peripheral blood B, CD4 + T, and CD8 + T lymphocytes, as well as switched memory B cells, are primarily targeted by the injection-only mechanism, as are B and T lymphocytes extracted from human colonic tissue, i.e.…”
Section: T3ss-mediated Subversion Of Adaptive Immunity: An As Of Yet mentioning
confidence: 99%
“…These findings reveal that through this mechanism, Shigella targeting can be extended to a large diversity of host cells, including those refractory to invasion. 65 Furthermore, B cells were shown to undergo apoptosis after the activation of a TLR2-dependent signaling pathway triggered by the T3SS needle-tip protein, revealing a Shigella targeting mechanism that is independent of both invasion and T3SS effector injection. 66 Consequently, we propose an additional mode of Shigella pathogenicity, termed the "kiss-and-run" strategy, describing the ability of Shigella to target cells via a T3SSdependent contact, which results in either effector interaction Note.…”
Section: T3ss-mediated Subversion Of Adaptive Immunity: An As Of Yet mentioning
confidence: 99%
“…On the opposite, the EPEC and EHEC effector EspG induces Golgi fragmentation, therefore disrupting the secretory pathway, similar to what is observed with Shigella(Clements et al, 2011).The consequences of Shigella-mediated increase in F-actin content and cellular stiffness along with impairment of vesicular trafficking in invaded T cells are likely responsible for the limitation in the formation of canonical IS while encountering with APCs and for the subsequent blockage of T cell activation we observed. Of note, besides the invaded T lymphocytes, it is likely that T lymphocytes targeting via the injection of T3SS effectors not resulting in bacterial invasion(Pinaud et al, 2017) further does its part in the prevention of T cell activation. The role in conjugates formation of some T3SS effectors known to mediate actin cytoskeleton rearrangements, such as IpgD(Konradt et al, 2011) tested for T cell stiffness, IpgB1B2, IcsB, and IcsA(Liu et al, 2018;Mattock & Blocker, 2017;Valencia-Gallardo et al, 2015) was assessed by using Shigella strains defective for their expression.…”
mentioning
confidence: 99%